Mycovirus-encoded suppressors of RNA silencing: Possible allies or enemies in the use of RNAi to control fungal disease in crops - Lorena Rodriguez Coy; Kim M. Plummer; Mahmoud E. Khalifa; Robin M. MacDiarmid; Robin M. MacDiarmid (Frontiers in Fungal Biology, 2022)
Plants, fungi, and many other eukaryotes have evolved an RNA interference (RNAi) mechanism that is key for regulating gene expression and the control of pathogens. RNAi inhibits gene expression, in a sequence-specific manner, by recognizing and deploying cognate double-stranded RNA (dsRNA) either from endogenous sources (e.g. pre-micro RNAs) or exogenous origin (e.g. viruses, dsRNA, or small interfering RNAs, siRNAs). Recent studies have demonstrated that fungal pathogens can transfer siRNAs into plant cells to suppress host immunity and aid infection, in a mechanism termed cross-kingdom RNAi. New technologies, based on RNAi are being developed for crop protection against insect pests, viruses, and more recently against fungal pathogens. One example, is host-induced gene silencing (HIGS), which is a mechanism whereby transgenic plants are modified to produce siRNAs or dsRNAs targeting key transcripts of plants, or their pathogens or pests. An alternative gene regulation strategy that also co-opts the silencing machinery is spray-induced gene silencing (SIGS), in which dsRNAs or single-stranded RNAs (ssRNAs) are applied to target genes within a pathogen or pest. Fungi also use their RNA silencing machinery against mycoviruses (fungal viruses) and mycoviruses can deploy virus-encoded suppressors of RNAi (myco-VSRs) as a counter-defence. We propose that myco-VSRs may impact new dsRNA-based management methods, resulting in unintended outcomes, including suppression of management by HIGS or SIGS. Despite a large diversity of mycoviruses being discovered using high throughput sequencing, their biology is poorly understood. In particular, the prevalence of mycoviruses and the cellular effect of their encoded VSRs are under-appreciated when considering the deployment of HIGS and SIGS strategies. This review focuses on mycoviruses, their VSR activities in fungi, and the implications for control of pathogenic fungi using RNAi.